Determinan Kepuasan Penggunaan Pembayaran Menggunakan OVO Pada Pengguna Transportasi Online - Eko Retno Indriyarti; Sri Wijihastuti (FEB Universitas Sam Ratulangi Manado, 2022)
In Indonesia, a wide range of cashless payment systems have been combined with a variety of applications, including online commerce, financial technology, and online transportation. Online transportation service providers, on the other hand, continue to accept cash payments for online transportation. In the middle of online transportation service providers' efforts to develop customer happiness initiatives, they must also be prepared to anticipate customer decisions to switch from cash to cashless payment methods. This is something that online transportation service providers should think about. Based on these findings, the purpose of this study is to determine the elements that influence customer satisfaction when applying the OVO payment method for online transportation. This quantitative notion is used in research that involves 146 samples to be analyzed with SMART PLS 3.0. The findings of this study show that the switching load has a substantial impact on youthful users of online transportation in Jakarta's desire to switch payment methods to OVO. Furthermore, this study demonstrates that the switching burden has no substantial impact on young users' happiness with OVO payment methods for online transportation in Jakarta. The study's third finding reveals that online transportation users in Jakarta's desire to switch to an OVO payment method has a substantial impact on their satisfaction with the service. According to the findings, there is a considerable effect of the desire to switch on user satisfaction, which can be used as a signal for service providers to consider attraction elements for switching, such as cheaper promotional programs than competitors.